33+(-7)=29+m

Simple and best practice solution for 33+(-7)=29+m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 33+(-7)=29+m equation:


Simplifying
33 + (-7) = 29 + m
33 + -7 = 29 + m

Combine like terms: 33 + -7 = 26
26 = 29 + m

Solving
26 = 29 + m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
26 + -1m = 29 + m + -1m

Combine like terms: m + -1m = 0
26 + -1m = 29 + 0
26 + -1m = 29

Add '-26' to each side of the equation.
26 + -26 + -1m = 29 + -26

Combine like terms: 26 + -26 = 0
0 + -1m = 29 + -26
-1m = 29 + -26

Combine like terms: 29 + -26 = 3
-1m = 3

Divide each side by '-1'.
m = -3

Simplifying
m = -3

See similar equations:

| -33+(-7)=29 | | 14y-4=3y | | 2x^2+(3x-5)=37 | | (3x^4+4x^3-5)-(8x^2-5x+8)= | | x-7y-14=0 | | x+2y=-13 | | 176=H+(219) | | (2x^2)=(3x^2-64) | | y=6x+b | | b=y-6x | | 2x+y=-14 | | 3+(4z+5)=31 | | 30x^2+27x= | | x/6-4=x/6 | | abs(2x-3)=4 | | 6x+17=4x+9 | | 9(x+2)=81(x+1) | | 4y^2-1=15 | | -2(3x-2)+X+9X=-3 | | -16x^2+400=0 | | 3y=81 | | cos(x)*cosh(x)=1 | | 2x^2+9x+2= | | 2000+Y=9500 | | -x^2-3x+3=0 | | 3x*x+27x=0 | | 3x*x+27=0 | | 3c^2=-16c+5 | | n+40=11q+9 | | 2m+3=7 | | 4(m+2)=40 | | 3x^3+25x^2+8x=0 |

Equations solver categories